PEMBINGKAIAN GAMBAR BERITA DI METROTV DAN RCTI MENJELANG PILKADA DKI JAKARTA 2017 - Zairiyah, Ulfa Aci; Sjafi'i, Achmad (Seni Media Rekam ISI Surakarta, 2017)
Framing images is one way used by MetroTV and RCTI in proclaiming Elections of DKI Jakarta. The goal is to build the public opinion.This study was conducted to find out the news ahead of Jakarta elections framed by Metro TV and RCTI.This research uses Gamson and Modigliani framing analysis model. The research method used is descriptive qualitative with sample impressions dated 5-13 October 2016.The technique of taking data using purposive samplingwhich is reinforced by observation and literature study.Data analysis used is interactive model of Miles and Huberman which is divided into three components, namely data reduction, data presentation, and conclusion and verification.The results show that Metro TV and RCTI do framing news images with impressive support and anti-support on shooting techniques.The shooting techniques include image size, image taking angle, image composition, and camera movement.MetroTV and RCTI proved to override the principle of journalism (cover both side) on news ahead of Elections DKI Jakarta.Keywords: Framing, news images,MetroTV,RCTI,and DKI Elections.